2015
DOI: 10.3109/13625187.2015.1059416
|View full text |Cite
|
Sign up to set email alerts
|

Differences in reporting Pearl Indices in the United States and Europe: Focus on a 91-day extended-regimen combined oral contraceptive with low-dose ethinyl estradiol supplementation

Abstract: Background Regulatory agencies in the United States (US) and Europe differ in requirements for defining pregnancies after the last dose of oral contraceptive, sometimes resulting in discrepant Pearl Indices (PIs) for the same product despite identical clinical data. This brief report highlights one such example, a 91-day extended-regimen combined oral contraceptive (COC). Methods The US- and European-based PI methodologies were compared for a 91-day extended-regimen COC consisting of 84 days of active levono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Similar to findings from other investigations, the youngest participants in our study had the highest contraceptive failure rates 20, 21. The higher pregnancy rate at US versus European sites is also consistent with results from other contraceptive studies,22, 23 and might reflect regional differences in following instructions for contraceptive use.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to findings from other investigations, the youngest participants in our study had the highest contraceptive failure rates 20, 21. The higher pregnancy rate at US versus European sites is also consistent with results from other contraceptive studies,22, 23 and might reflect regional differences in following instructions for contraceptive use.…”
Section: Discussionsupporting
confidence: 92%
“…This corpus, composed of articles testing the efficacy of Pediatric HAART, sought to evaluate the linguistic framing of studies originating from either the United States or Europe. We intentionally selected this comparison to compliment the extended history of comparative EU/US medical research (Philipson, 2005 ; Lobo Abascal et al, 2016 ), in addition to the high rate at which studies in either region publish in the English language. To compose this corpus, we searched PubMed, EbscoHost, Web of Science, and Medline using various iterations of pediatric (or paediatric) HAART, including infant HAART and perinatal HAART.…”
Section: Methodsmentioning
confidence: 99%
“…Abascal reported that for a 91-day extended-regimen COC containing 150 μg of levonorgestrel and 30 μg EE, the US study reported a PI of 1,34 and the European study a PI of 0,76. In this scenario, the US study included all the pregnancies that happened up to 14 days after the end of the study, unlike the European study that only included pregnancies occurring up to 2 days after the end of the study [14].…”
Section: Effectiveness Of Oral Contraceptives: the Pearl Indexmentioning
confidence: 97%